A mutation affecting laminin alpha 5 polymerisation gives rise to a syndromic developmental disorder. - Jones, Lynelle K; Lam, Rachel; McKee, Karen K; Aleksandrova, Maya; Dowling, John; Alexander, Stephen I; Mallawaarachchi, Amali; Cottle, Denny L; Short, Kieran M; Pais, Lynn; Miner, Jeffery H; Mallett, Andrew J; et al. (Development, 2020)
Laminin alpha 5 (LAMA5) is a member of a large family of proteins that trimerise and then polymerise to form a central component of all basement membranes. Consequently, the protein plays an instrumental role in shaping the normal development of the kidney, skin, neural tube, lung and limb, and many other organs and tissues. Pathogenic mutations in some laminins have been shown to cause a range of largely syndromic conditions affecting the competency of the basement membranes to which they contribute. We report the identification of a mutation in the polymerisation domain of LAMA5 in a patient with a complex syndromic disease characterised by defects in kidney, craniofacial and limb development, and by a range of other congenital defects. Using CRISPR-generated mouse models and biochemical assays, we demonstrate the pathogenicity of this variant, showing that the change results in a failure of the polymerisation of α/β/γ laminin trimers. Comparing these phenotypes with those apparent upon gene deletion in mice provides insights into the specific functional importance of laminin polymerisation during development and tissue homeostasis.
Keywords: Amino Acid Sequence; Animals; Animals, Newborn; Child, Preschool; Developmental Disabilities; Fetal Development; Fetus; Humans; Hydronephrosis; Infant, Newborn; Kidney; Laminin; Lung; Male; Mice; Mutation; Polymerization; Protein Domains; Syndrome